Delirium in the United States: results from the 2023 cross-sectional World Delirium Awareness Day prevalence study - Lindroth, Heidi; Byrnes, Tru; Fuchita, Mikita; Hetland, Breanna; Liu, Keibun; Maya, Kerri; McAndrew, Natalie S.; Mulkey, Malissa A.; Nydahl, Peter; Palakshappa, Jessica; Haken, Rebecca von; Psoter, Kevin J.; et al. (Journal of the Academy of Consultation-Liaison Psychiatry, 2024)
Background - Delirium is an acute brain dysfunction associated with an increased risk of mortality and future dementia. - Objectives - To describe the prevalence of clinically documented delirium in the United States on World Delirium Awareness Day 2023. - Methods - This is a sub-analysis of a prospective, cross-sectional, online, international survey. All health care settings were eligible, with the exception of operating rooms and outpatient clinics. Health care clinicians, administrators, and researchers completed the survey. The primary outcome was the prevalence of clinically documented delirium at 8:00 a.m. and 8:00 p.m. on March 15, 2023. Secondary outcomes were related to health care delivery. Descriptive statistics are reported. Differences between unit types (non-intensive care unit vs intensive care unit) were examined for all outcomes. - Results - Ninety-one hospital units reported on 1318/1213 patients. The prevalence of clinically documented delirium was 16.4% (n = 216/1318) at 8:00 a.m. and 17.9% (n = 217/1213) at 8:00 p.m. (P = 0.316) and significantly differed between age groups, reported discipline, unit, and hospital types. Significant differences were identified between non-intensive care unit and intensive care unit settings in the use of delirium-related protocols, nonpharmacologic and pharmacologic management, educational processes, and barriers to evidence-based delirium care. - Conclusions - To our knowledge, this is the first epidemiologic survey of clinically documented delirium across two time points in the United States. Delirium remains a significant burden and challenge for health care systems. The high percentage of units using delirium management protocols suggests administrator and clinician awareness of evidence-based strategies for its detection and mitigation. We provide recommendations for future studies and quality improvement projects to improve clinical recognition and management of delirium.